Use of beta blockers in dilated cardiomyopathy and relationship with cardiovascular events. (25th November 2020) - Vallejo Garcia, V; Gonzalez Calle, D; Castro Garay, J.C; Garcia Monsalvo, M; Borrego Rodriguez, J; Barreira De Sousa, G; Rodriguez Estevez, L; Nunez Garcia, J; Luengo Mondejar, P; Antunez Ballesteros, M; Hernandez Hidalgo, M; Cruz Gonzalez, I; et al.
Abstract:  : There is an ongoing debate regarding the use of beta blockers (BB) in heart failure with preserved or intermediate ejection fraction. Most studies with BB included patients with moderate to severe left ventricle (LV) dysfunction and some trials challenge the assumption that BB are an effective therapy in these patients. Furthermore, there are some causes of heart failure where the use of BB is not well defined, particularly patients with DCM and mildly reduced LV ejection fraction. Our objective was to analyze the use of beta blockers in patients with dilated cardiomyopathy and to assess its relationship with LV or right ventricle (RV) ejection fraction, late gadolinium enhancement and cardiovascular events (CVE). A retrospective, case control study was designed including 173 patients (mean age 60 years, 73% males, 36% dyslipemia, 30% diabetes, 20% hypertension, 8% currents smoker, 12% previous atrial fibrillation) with diagnosis of DCM and CMR study in our center between 2014–2020 according to the latest European Society of Cardiology (ESC) definition and the latest updated position paper. Clinical data, use of guideline directed medical therapy and devices, cardiac imaging tests, mortality and CVE were collected and analyzed. After a mean follow up of 18 months, 53 patients (30%) suffered a CVE (16% heart failure, 14% incident arrythmia, 0.5% stroke 8% death). The use of beta blockers (n=152; 87%) was associated with a reduced risk for arrythmias (OR=0.019; p=0.0006) in a univariate analysis. It was not associated with RV ejection fraction (p=0.3), hospitalization for heart failure (p=0.03), mortality (p=0.26), or late gadolinium enhancement (p=0.8). For multivariate analyses (log regression, multiple linear regression) we adjusted for age, cardiovascular risk factors, medications, presence of atrial fibrillation, use of devices, LV and RV ejection fraction and presence of late gadolinium enhancement. In our multivariate analyses the use of beta blockers was an independent predictor of improved left ventricle ejection fraction (5.8% mean; p=0.009) and was associated with a marked decrease in the risk of incident arrythmias (OR=0.028; p=0.002) and in mortality (OR=0.068; p=0.041). In patients with DCM, the use of beta blockers is associated with improved LV ejection fraction and a statistically significant reduction in mortality and incident arrythmias. Beta blockers should be recommended irrespective of LV ejection fraction in order to decrease morbidity and mortality in patients with dilated cardiomyopathy. Further studies should assess the contribution of beta blockers in specific etiologies of dilated cardiomyopathy where they could be most helpful and could help to identify the best candidates for early initiation of heart failure therapy. Funding Acknowledgement: Type of funding source: None